2006
DOI: 10.1017/s0033291706009111
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex dysfunction in patients with suicidal behavior

Abstract: These deficits are consistent with prefrontal dysfunction in patients with suicidal behavior. Differentiation between DLPFC- and OFC-related neuropsychological functions showed no specific dysfunction of the orbitofrontal region in patients with suicidal behavior in our sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 47 publications
1
51
1
4
Order By: Relevance
“…It is difficult to say to what extent our results affect the interpretation of earlier findings of association of suicide attempt history with executive impairment in younger individuals (10, 15, 35), not only because of the difference in age, but also because different tests were used. A conservative conclusion would be that the stage of the suicidal process where executive deficits may play a role is yet to be established.…”
Section: Discussionmentioning
confidence: 57%
“…It is difficult to say to what extent our results affect the interpretation of earlier findings of association of suicide attempt history with executive impairment in younger individuals (10, 15, 35), not only because of the difference in age, but also because different tests were used. A conservative conclusion would be that the stage of the suicidal process where executive deficits may play a role is yet to be established.…”
Section: Discussionmentioning
confidence: 57%
“…41 Therefore, OFC and VPC dysfunction in alexithymics may cause a perturbation of HPA functioning, leading to a dyslipidemia that may be associated with increased suicidal ideation. 42 However, the relationships between alexithymia, serum lipid levels, and suicidal ideation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(Kessler et al, 1999;Coryell and Young, 2005). Several studies have demonstrated the relationship between impulsivity and suicide (Baca-Garcia et al, 2005;Raust et al, 2006). Particularly a recent report found the relationship between impulsive action and suicide attempts in bipolar disorder patients (Swann et al, 2005).…”
Section: Introductionmentioning
confidence: 97%